Association of Seat Height and Arm Position on the Five Times Sit-to-Stand Test Times of Stroke Survivors. (10th September 2013) - Ng, Shamay S. M.; Cheung, Susanna Y.; Lai, Lauren S. W.; Liu, Ann S. L.; Ieong, Selena H. I.; Fong, Shirley S. M.
Abstract : Objectives . To investigate (1) the association of seat height and (2) the association of arm position on the five times sit-to-stand test (FTSTS) times of individuals with stroke. Design . A cross-sectional study. Setting . University-based rehabilitation centre. Subjects . Patients (n = 43 ) with chronic stroke. Methods . The times in completing the FTSTS with different seat height (85%, 100%, and 115% knee height) and arm positions (arms across chest, hands on thighs). Results . FTSTS times were significantly different between 85% and 100% seat heights, and between the 85% and 115% seat heights in both arm positions. However, there was no significant difference between the FTSTS times with the two arm positions at any seat height tested. Conclusion . Seat heights lower than the knee height result in longer FTSTS times, whereas arms positions did not significantly affect the FTSTS times.